Effectiveness of olive oil administration on stretch mark reduction in postpartum women - Nurwendah, Siti; Manullang, Riyen Sari; Br Karo, Marni; Santosa, Puji Raharja; Silitonga, Riris Ocktryna (PT. Mega Science Indonesia, 2025)
Stretch marks manifest as hyperpigmented dermal lesions that commonly occur during pregnancy. These cutaneous changes frequently cause physical discomfort and psychological distress among postpartum women, leading to diminished self-esteem and social withdrawal. Nonpharmacological interventions, particularly olive oil application, are potentially effective management approaches. This study evaluated the efficacy of topical olive oil in reducing stretch mark visibility among postpartum women in the Karang Mulya Community Health Center service area in 2024. This quantitative investigation employed a quasi-experimental design with pre- and posttest assessments. The participants included 45 postpartum women on postpartum day 6 residing within the Karang Mulya Health Center catchment area in March 2024. A total sampling technique was used, and data collection relied on standardized observational assessment tools. Statistical analysis was performed via the Mann‒Whitney test (p<0.05). The baseline assessment revealed a mean stretch mark severity score of 3.87 (SD=1.407) before olive oil application, which decreased significantly to 1.07 (SD=0.799) after the intervention. The experimental group demonstrated a statistically significant improvement compared with the control group (p<0.001), confirming marked differences in the visibility of stretch marks following olive oil treatment. Topical olive oil application significantly reduces stretch mark visibility in postpartum women. These findings support the implementation of this technique as a safe and accessible nonpharmacological intervention in postpartum care protocols for stretch mark management.